Predictors of survival in paediatric mitral valve replacement. (14th February 2021) - Brancaccio, Gianluca; Trezzi, Matteo; Chinali, Marcello; Vignaroli, Walter; D'Anna, Carolina; Iodice, Francesca; Giorni, Chiara; Iacobelli, Roberta; Iorio, Fiore; Galletti, Lorenzo; Croci, Ileana; Carotti, Adriano
Abstract:  : OBJECTIVES: The aim of this study was to identify the predictors of death and of reintervention after mitral valve replacement (MVR) in children. METHODS: A single-centre retrospective study was performed including 115 patients under the age of 18 undergoing MVR between 1982 and 2019. For all patients, the ratio of prosthetic valve size (diameter in mm) to weight (kg) at surgery was calculated and long-term result was assessed. The primary outcome was freedom from mitral valve (MV) re-replacement. The composite secondary outcome was freedom from death or transplant. RESULTS: Fifty-four patients had a previous surgical attempt to MV repair. The median age at surgery was 5.5 years (interquartile range 1.21–9.87). Death/transplant-free survival was 77 ± 4% at 5 years and 72 ± 5% at 10 years. Univariate analysis showed a size/weight ratio higher than 2 and age <2 years as significant risk factors for death or transplant. Freedom from MV re-replacement at 5 and 10 years was 90 ± 3% and 72 ± 6%, respectively. Biological prosthesis implanted at first replacement ( P  = 0.007) and size/weight ratio higher than 2 ( P  = 0.048) were predictors of reoperation. Significant upsizing ( P  < 0.0001) of mitral prosthesis was observed at re-replacement. CONCLUSIONS: MVR is a viable strategy in children with unrepairable MV disease. Mortality can be predicted based on size/weight ratio and age <2 years. MV re-replacement can be performed with low morbidity and mortality and a larger-size prosthesis can often be placed at the time of redo.